The Stress Intensity Factor of convex embedded polygonal cracks (Fracture and Structural Integrity, 2022)
In the present work, a simple formula for the evaluation of the stress intensity factor (SIF) of convex embedded polygonal cracks has been proposed. This formula is structured as a correction factor of the Oore-Burns’ equation and is based on accurate three-dimensional FE analysis. Furthermore, a precise formula for a regular polygonal crack has been given.
Keywords: Weight function; Stress intensity factor; Three-dimensional crack